Optimization of Warehouse Performance through Class-Based Storage based FSN Analysis for Travel Efficiency and Cost Reduction - Abdul Lathif; Said Salim Dahda; Deny Andesta (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study aims to optimize operational efficiency at PT XYZ's raw material warehouse by mitigating high material handling costs (MHC) and inefficient forklift travel caused by random storage and LIFO stacking constraints. The research proposes a warehouse layout redesign applying a Class-Based Storage (CBS) strategy zoned via FSN (Fast, Slow, Non-moving) analysis. The methodological approach involves material flow analysis of 31 SKUs, priority classification based on Turnover Ratio (TOR), and simulation of rectilinear distances and travel times using a standard speed of 1.4 m/s. Through comparative evaluation, the study found that the strategic relocation of 14 Fast-category items to zones closest to the Inbound/Outbound point successfully reduced monthly travel distance from 11,261.3 m to 9,557.3 m. This directly impacted operational time, reducing it by 0.34 hours, and lowered total MHC by 15.13%, equivalent to a monthly saving of IDR 1,610,231. The results conclude that FSN-activity-based zoning not only quantitatively reduces logistical costs but also qualitatively minimises aisle congestion and non-value-added backtracking movements, thereby enhancing overall warehouse productivity.